2018
DOI: 10.1039/c8ra01988f
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous supercapacitors based on carbonized silk electrodes

Abstract: Graphitic nitrogen-doped hierarchical porous carbon nanosheets for supercapacitor application were derived from an easily obtained and green silk by simultaneous ZnCl 2 activation and FeCl 3 graphitization at different heating temperatures. By increasing the heating temperature from 700 to 850 C, the degree of graphitization and BET surface area rose to their highest levels, while the nitrogen doping content was maintained at 2.24 wt%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 67 publications
0
10
0
Order By: Relevance
“…Even at a high power density of 25009 W kg –1 , the energy density of C-SPIO@4 still reached 31.7 Wh kg –1 . Such results are much better than those of carbonized SF-based, N-doped nanoporous carbon originating from organic compounds and IO-based nanoporous carbon for SC electrodes. , Comparisons of the electrochemical performances of C-SPIO@4 with those reported in the literature are listed in Table S2. It is understood that the capacitances of these heteroatom-doped carbon materials showed high energy densities at small current densities but declined significantly at higher current densities.…”
Section: Resultsmentioning
confidence: 97%
“…Even at a high power density of 25009 W kg –1 , the energy density of C-SPIO@4 still reached 31.7 Wh kg –1 . Such results are much better than those of carbonized SF-based, N-doped nanoporous carbon originating from organic compounds and IO-based nanoporous carbon for SC electrodes. , Comparisons of the electrochemical performances of C-SPIO@4 with those reported in the literature are listed in Table S2. It is understood that the capacitances of these heteroatom-doped carbon materials showed high energy densities at small current densities but declined significantly at higher current densities.…”
Section: Resultsmentioning
confidence: 97%
“…Furthermore, rGO@Hh and Ni (OH) 2 /rGO@Hh fibers were used as negative and positive electrodes in a solid-state fiber-based asymmetric supercapacitor (FASC), which showed high energy of 27.6 Wh/kg and a power density of 699 W/kg, respectively. In addition, Zhang et al [ 56 ] reported on simultaneous ZnCl 2 activation and FeCl 3 graphitization at varied heating temperatures. This yielded graphitic nitrogen-doped hierarchical porous carbon nanosheets and was employed for supercapacitor application from a readily produced green silk, as shown in Figure 8 e. The degree of graphitization and BET surface area increased to their greatest values when the heating temperature was increased from 700 °C to 850 °C, while the nitrogen doping concentration was kept at 2.24 wt%.…”
Section: Recent Advancements In Biopolymers-derived Materials For Sup...mentioning
confidence: 99%
“…( e ) Silk synthesis method. Adapted from reference [ 56 ]. This article is an open-access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY 3.0) license.…”
Section: Figurementioning
confidence: 99%
“…2g) found for SA-1500 at $2700 cm −1 indicates the formation of graphene-like nanostructures. 39 In order to further identify the elemental composition of the SA, XPS patterns are shown in Fig. S6 † and Fig.…”
Section: Fabrication and Characterization Of Silk Derived Carbon Bre...mentioning
confidence: 99%